Normal-temperature high-humidity-resistant ozonolysis catalyst as well as preparation method and application thereof

The synthetic MnCo2O4.5 catalyst with a three-dimensional square structure was solved by the rheological phase method, and the problems of insufficient ozone decomposition efficiency at room temperature and the lack of moisture resistance of manganese oxide catalysts were achieved, and the ozone decomposition effect was achieved.

CN119680564AActive Publication Date: 2025-03-25SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411454758.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-25
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently decompose ozone at room temperature, and the manganese oxide catalyst lacks moisture resistance under high humidity conditions, which hinders its industrial application.

Method used

The manganese cobalt bimetallic catalyst was synthesized by rheology phase method, and the metal salt and the chelating agent were chelated by grinding, and the solvent was added to make the mixture in the rheology phase, and then heated and activated to prepare a MnCo2O4.5 catalyst with a three-dimensional square structure.

Benefits of technology

It achieves efficient decomposition of ozone at room temperature, with a decomposition rate of 100%, and maintains stable and efficient operation for at least 100 hours under high humidity conditions, significantly improving the moisture resistance and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680564A_ABST
    Figure CN119680564A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a normal-temperature high-humidity-resistant ozonolysis catalyst, the catalyst is synthesized by a simple rheological phase method, and a bimetallic oxide is mainly formed by Co and Mn. The obtained catalyst with the optimal performance can achieve the ozone removal efficiency close to 100% under the conditions of normal temperature and high humidity, and can keep stable and efficient operation for at least 100 h. The method has the advantages of energy conservation, high efficiency, short steps, greenness and no pollution, and does not use any polluting solvent such as a surfactant or a template except water. The catalyst can be widely applied to various low-concentration ozone pollution sources, such as air purifiers, sterilization and disinfection cabinets, printers, and terminal ozonolysis such as ultraviolet photolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and relates to a preparation method and application of an ozone decomposition catalyst. Background Art

[0002] Excessive near-ground ozone concentrations have always posed a threat to human health, especially in urban areas. Outdoor ozone is mainly produced by the photochemical reaction of nitrogen oxides with volatile organic pollutants (VOCs) in the air under sunlight. Ozone has excellent bactericidal and disinfecting properties, and the inactivation reaction is rapid. The good bactericidal and disinfecting effect makes ozone widely used in the medical and health field. Indoor ozone comes from indoor and outdoor air exchange. There are also some emission sources including copiers, laser printers, ultraviolet lamps and ozone disinfectants. The widespread use of electrical appliances in daily life makes ozone one of the main air pollutants in modern society. Although as a strong oxidant, ozone has strong reactivity, it is relatively stable in itself and will hardly spontaneously decompose into oxygen at the concentrations commonly encountered in ambient air (ppb level). And ozone can have an adverse effect on the growth of plants, insects and soil microbial communities, threatening terrestrial ecosystems and ecological diversity. In addition, indoor ozone sources can also cause secondary organic aerosol pollution, which is harmful to human health. A large number of studies have shown that long-term exposure to air containing trace amounts of ozone will cause potential risks of respiratory and cardiovascular diseases and even death to the human body. In addition, long-term inhalation of secondary pollutants produced by the reaction of ozone with other chemicals can even cause irreversible damage to the DNA of organisms. However, in the past few years, the occurrence of severe ozone pollution in the warm season has become more frequent. Therefore, there is an urgent need to develop efficient and environmentally friendly ozone removal methods.

[0003] Ozone decomposition methods mainly include thermal decomposition, activated carbon, liquid absorption and catalytic decomposition. Thermal decomposition is usually suitable for the treatment of high-concentration industrial waste gas, and the required conditions are harsh, usually requiring a high temperature of more than 400°C; although the activated carbon method is suitable for low-concentration ozone decomposition, it is easy to deactivate and has poor water resistance; the liquid absorption method will have problems such as waste liquid causing secondary pollution; the catalytic decomposition method can better make up for the shortcomings of the above methods, and has the advantages of low energy consumption, rapid reaction and high treatment efficiency. Therefore, the catalytic decomposition of ozone is the key to controlling ozone pollution. The key to catalytic decomposition technology lies in the performance of the catalyst. Therefore, it is urgent to develop a room temperature and high humidity resistant ozone decomposition catalyst.

[0004] CN117861681A discloses an ozone decomposition catalyst, a preparation method and an application thereof. The catalyst is a layered metal hydroxide with a hydrotalcite structure. The preparation method comprises: obtaining a positive electrode sheet of a waste lithium manganese oxide battery and crushing it to obtain a positive electrode active powder; treating the positive electrode active powder with a leaching agent and a reducing agent to obtain a leaching solution with a volume ratio of (90-110):(4-6) at 60-80°C for 1-5h and filtering; first adding deionized water to the filtrate to adjust the pH to 3-4, and then adding nickel metal salt to the filtrate, wherein the molar ratio of nickel element, manganese element and copper element is (2.5-3.5):1:(0.02-0.05); finally adding H2O2 solution and urea, heating at 110-130°C for 11-13h, and then drying at 55-65°C for 6-12h to obtain an ozone decomposition catalyst.

[0005] CN115417941A discloses a catalyst suitable for ozone decomposition in an atmospheric environment and its application. The preparation method comprises: mixing azobisisobutyronitrile, ethylene glycol dimethacrylate and toluene in a certain proportion, and causing precipitation polymerization reaction at 60-70°C in the absence of oxygen for 5-20 hours; after the reaction is completed, removing most of the organic solution by vacuum filtration, and transferring the obtained polymer (i.e., polyethylene glycol dimethacrylate) solid to a vacuum drying oven for drying to obtain the catalyst.

[0006] CN116726911A discloses a Mn5O8 ozone room temperature decomposition catalyst and a preparation method thereof. The preparation method comprises: mixing potassium permanganate and manganate with solid organic acid, solid phase grinding for 1-5 minutes, heating at 60-120°C for 0.5-2h to obtain a fluffy precursor; cooling the precursor, adding the precursor into distilled water, stirring evenly, heating at 80-200°C for activation for 0.5-3h, cooling, filtering, washing and drying to obtain the Mn5O8 ozone room temperature decomposition catalyst.

[0007] Manganese oxides are polymorphic and are considered to be the most promising catalysts for ozone decomposition because of their different crystal structures, different manganese valence states, low cost and easy production. Although manganese oxides are widely used in the field of ozone catalysis / decomposition due to their high activity, their moisture resistance is poor and their catalytic activity under high humidity conditions is not satisfactory, which hinders their industrial application. Therefore, improving the water resistance of manganese-based catalysts is the key to solving the application of ozone decomposition catalysts. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a room temperature and high humidity resistant ozone decomposition catalyst. The catalyst can achieve high efficiency ozone decomposition at room temperature, and the decomposition rate reaches 100%, and has the advantages of long catalytic life and high humidity resistance.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0010] In a first aspect, the present invention provides a method for preparing a room temperature and high humidity resistant ozone decomposition catalyst, the preparation method comprising the following steps:

[0011] (1) grinding cobalt nitrate and a chelating agent in a mortar, then adding a nitrate precursor of the Mn element, adjusting the rheological phase and continuing grinding;

[0012] (2) As the liquid water content decreases during the grinding process, a small amount of solvent is added to fully grind to obtain a rheological phase mixed metal solution;

[0013] (3) The rheological phase mixed metal solution obtained by grinding is transferred to a reaction tank, heated and activated in an oven, and then sequentially subjected to solid-liquid separation, washing, drying, and calcination to obtain the catalyst.

[0014] The present invention adopts a simple rheological phase method to synthesize a manganese-cobalt bimetallic catalyst. The metal salt and the chelating agent are ground to undergo a chelation reaction, a solvent is added to put the mixed solution in a rheological phase, and then heated and activated to improve the catalytic activity and stability of the prepared catalyst. The method is not only energy-saving and efficient, but also has short steps and is green and pollution-free. In addition to water, no polluting solvents such as surfactants or templates are used.

[0015] Preferably, the chelating agent in step (1) is oxalic acid dihydrate.

[0016] Preferably, in step (1), the nitrate precursor of the Mn element is: a manganese nitrate solution with a mass percentage concentration of 50%.

[0017] Preferably, the molar ratio of cobalt nitrate to chelating agent oxalic acid dihydrate in step (1) is (0.8-1.2):1.

[0018] Preferably, the solvent in step (2) is deionized water.

[0019] Preferably, the conditions for heating and activating the rheological phase mixed metal solution in step (3) are: 100-110° C., 7-9 h.

[0020] Preferably, the molar ratio of cobalt element to manganese element in the rheological phase mixed metal solution is 1:(4.5-5.5).

[0021] Preferably, the drying conditions are: 100-110° C., 11-13 h.

[0022] Preferably, the calcination conditions are: 450-550°C, 5-7h.

[0023] In the second aspect, the present invention provides a catalyst for ozone decomposition at room temperature and high humidity, wherein the catalyst is a bimetallic oxide having a three-dimensional square structure, wherein the bimetallic elements are cobalt and manganese respectively; and the specific bimetallic structure of the catalyst is MnCo2O 4.5 , its specific surface area is 113.35m 2 / g.

[0024] The catalyst with the best performance obtained by the present invention can achieve a removal efficiency of nearly 100% for ozone under normal temperature and high humidity conditions, and maintain stable and efficient operation for at least 100 hours.

[0025] In a third aspect, the present invention provides an application of a room temperature and high humidity resistant ozone decomposition catalyst, wherein the ozone decomposition catalyst is used to catalytically decompose ozone. The present invention can be applied to various low-concentration ozone pollution sources, such as air purifiers, sterilization cabinets, printers, and terminal ozone decomposition such as ultraviolet photolysis.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention adopts a rheological phase method to prepare the catalyst, which has a simple preparation process and is easy to realize industrialization;

[0028] (2) The active components of the present invention are all non-precious metals, and the raw materials are cheap, which greatly reduces the production cost;

[0029] (3) The catalyst of the present invention has a unique three-dimensional square structure, which improves the stability and moisture resistance of the catalyst while ensuring the ozone decomposition rate. It can ensure an ozone decomposition rate close to 100% under a 100h stability test and a 4vol% H2O humidity test;

[0030] (4) The present invention does not require complicated reaction conditions such as high temperature heating and high pressure, and the reaction can be completed at room temperature, which is safer;

[0031] (5) The present invention is not only energy-saving and efficient, but also has a short process. In addition to water, it does not use any polluting solvents such as surfactants or templates, and is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the XRD diagram of the room temperature and high humidity resistant ozone decomposition catalyst described in Example 1.

[0033] Figure 2 This is a SEM image of the room temperature and high humidity resistant ozone decomposition catalyst described in Example 1.

[0034] Figure 3 It is a comparison chart of the activities of the ozone decomposition catalysts prepared in Examples 1-5 at room temperature and dry conditions.

[0035] Figure 4 This is a comparison chart of the activities of the ozone decomposition catalysts prepared in Examples 1-5 at room temperature and 4 vol% H2O.

[0036] Figure 5 This is the ozone detection test paper diagram after the ozone decomposition catalyst prepared in Examples 1-5 was tested under 4 vol% H2O conditions.

[0037] Figure 6 This is a stability evaluation graph of the room temperature and high humidity resistant ozone decomposition catalyst described in Example 1 after reacting for 100 hours under dry and 4 vol% H2O conditions.

[0038] Figure 7 1 is the XRD diagram of the ozone decomposition catalyst described in Example 1 and Example 6.

[0039] Figure 8 is a SEM image of the ozone decomposition catalyst described in Examples 1-10. DETAILED DESCRIPTION

[0040] The following will be combined with the implementation cases of the present invention to clearly and completely describe the technical solutions in the implementation cases of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the scope of protection of the present invention.

[0041] Example 1

[0042] The method is a rheological phase method, and the preparation process is as follows:

[0043] 1.80 g of cobalt nitrate and 2.478 g of oxalic acid dihydrate were weighed, and the two were placed in a mortar and ground for 10 min. 7.2 mL of the nitrate precursor of the Mn element was added, and the rheological phase was adjusted to continue grinding. During the grinding, deionized water was continued to be added as the liquid water content decreased, and the grinding was fully carried out. The viscous paste obtained by grinding was transferred to a polytetrafluoroethylene reaction tank and heated and activated at 105 ° C for 8 h. After cooling, the solution in the tank was transferred to a beaker, and after solid-liquid separation, it was dried at 105 ° C for 12 h, and then placed in a muffle furnace and calcined at 500 ° C for 6 h to obtain MnCo2O 4.5 Ozone decomposition catalyst.

[0044] Example 2

[0045] The method is a rheological phase method, and the preparation process is as follows:

[0046] Weigh 2.69g of cerium nitrate and 2.478g of oxalic acid dihydrate, place the two in a mortar and grind for 10min, add 7.2mL of nitrate precursor of Mn element, adjust to rheological phase and continue grinding; during grinding, continue to add deionized water as the liquid moisture decreases, grind thoroughly, transfer the viscous paste obtained by grinding into a polytetrafluoroethylene reaction tank, and heat and activate at 105℃ for 8h; after cooling, transfer the solution in the tank to a beaker, dry at 105℃ for 12h after solid-liquid separation, and place in a muffle furnace and calcine at 500℃ for 6h to obtain a MnCe ozone decomposition catalyst.

[0047] Example 3

[0048] The method is a rheological phase method, and the preparation process is as follows:

[0049] 1.80 g of nickel nitrate and 2.478 g of oxalic acid dihydrate were weighed, placed in a mortar and ground for 10 min, 7.2 mL of a nitrate precursor of the Mn element was added, and the mixture was adjusted to a rheological phase and continued to be ground; deionized water was continuously added as the liquid moisture content decreased during grinding, and the mixture was fully ground. The viscous paste obtained by grinding was transferred into a polytetrafluoroethylene reaction tank and heated and activated at 105 °C for 8 h; after cooling, the solution in the tank was transferred to a beaker, dried at 105 °C for 12 h after solid-liquid separation, and placed in a muffle furnace and calcined at 500 °C for 6 h to obtain a MnNi ozone decomposition catalyst.

[0050] Example 4

[0051] The method is a rheological phase method, and the preparation process is as follows:

[0052] Weigh 1.50g of copper nitrate and 2.478g of oxalic acid dihydrate, place the two in a mortar and grind for 10 minutes, add 7.2mL of the nitrate precursor of the Mn element, adjust to the rheological phase and continue grinding; during grinding, continue to add deionized water as the liquid moisture decreases, grind thoroughly, transfer the viscous paste obtained by grinding into a polytetrafluoroethylene reaction tank, and heat and activate at 105°C for 8h; after cooling, transfer the solution in the tank to a beaker, dry at 105°C for 12h after solid-liquid separation, and place it in a muffle furnace and calcine at 500°C for 6h to obtain a MnCu ozone decomposition catalyst.

[0053] Example 5

[0054] The method is a rheological phase method, and the preparation process is as follows:

[0055] Weigh 2.478 g of oxalic acid dihydrate and mix it with 7.2 mL of Mn element nitrate precursor to form rheological phase grinding; during grinding, continue to add deionized water as the liquid moisture decreases, grind thoroughly, transfer the viscous paste obtained by grinding into a polytetrafluoroethylene reaction tank, and heat and activate it at 105°C for 8 hours; after cooling, transfer the solution in the tank to a beaker, dry it at 105°C for 12 hours after solid-liquid separation, and put it into a muffle furnace and calcine it at 500°C for 6 hours to obtain a Mn ozone decomposition catalyst.

[0056] Example 6

[0057] The catalyst is a sample of the catalyst obtained in Example 1 after being tested under 4 vol% H2O for 15 hours. The test conditions are: total gas flow rate of 1 L / min, 1.5 ppm O3, 4 vol% H2O, catalyst dosage of 0.04 g, reaction space velocity of 1500 L / (g·h) -1 , test temperature is room temperature.

[0058] Example 7

[0059] The catalyst is a sample of the catalyst obtained in Example 2 after being tested under 4 vol% H2O conditions for 15 hours. The test conditions are: total gas flow rate of 1 L / min, 1.5 ppm O3, 4 vol% H2O, catalyst dosage of 0.04 g, reaction space velocity of 1500 L / (g·h) -1 , test temperature is room temperature.

[0060] Example 8

[0061] The catalyst is a sample of the catalyst obtained in Example 3 after being tested under 4 vol% H2O conditions for 15 hours. The test conditions are: total gas flow rate of 1 L / min, 1.5 ppm O3, 4 vol% H2O, catalyst dosage of 0.04 g, reaction space velocity of 1500 L / (g·h) -1 , test temperature is room temperature.

[0062] Example 9

[0063] The catalyst is a sample of the catalyst obtained in Example 4 after being tested under 4 vol% H2O conditions for 15 hours. The test conditions are: total gas flow rate of 1 L / min, 1.5 ppm O3, 4 vol% H2O, catalyst dosage of 0.04 g, reaction space velocity of 1500 L / (g·h) -1 , test temperature is room temperature.

[0064] Example 10

[0065] The catalyst is a sample of the catalyst obtained in Example 5 after being tested under 4 vol% H2O conditions for 15 hours. The test conditions are: total gas flow rate of 1 L / min, 1.5 ppm O3, 4 vol% H2O, catalyst dosage of 0.04 g, reaction space velocity of 1500 L / (g·h) -1 , test temperature is room temperature.

[0066] Sample analysis

[0067] The XRD pattern of the room temperature and high humidity resistant ozone decomposition catalyst prepared in Example 1 is as follows: Figure 1 As shown, Figure 2 This is a SEM image of the room temperature high humidity resistant ozone decomposition catalyst prepared in Example 1. It can be seen that Example 1 is a MnCo2O with a three-dimensional square structure. 4.5 .

[0068] The molar ratio of Mn element to Co / Ce / Ni / Cu of the catalysts prepared in Examples 1-4 is (4.5-5.5):1.

[0069] The catalysts prepared in Examples 1-5 were placed in a fixed bed reactor for activity evaluation. The total flow rate of the simulated gas was 1 L / min, 1.5 ppm O3, dry / 4 vol% H2O, the catalyst dosage was 0.04 g, and the reaction space velocity was 1500 L / (g·h). -1 , the test temperature is room temperature. After 15h drying and 4vol% H2O conditions, the ozone decomposition performance of Examples 1-5 was tested. Figure 3 and 4 As shown in the figure, the sample with the highest ozone decomposition rate under both conditions is the sample of Example 1, and the decomposition rate is close to 100%. The ozone decomposition capacity of Example 1 can also be seen from the result of the ozone test paper ( Figure 5 ) proves. The sample of Example 1 was tested for stability and continuous water resistance. Figure 6 It can be seen that after running for 100 hours, the ozone decomposition rate can still be close to 100%. This proves that Example 1 has excellent stability and water resistance, and is not easy to denature and deactivate, which can also be seen from the sample before and after the reaction (MnCo2O 4.5 -F and MnCo2O 4.5 -U) XRD and SEM data ( Figure 7-8 ) was further verified.

[0070] Table 1 BET test results of the ozone decomposition catalysts prepared in Examples 1-5.

[0071]

Claims

1. A catalyst for ozone decomposition, characterized in that: The catalyst is a bimetallic oxide with a three-dimensional square structure, wherein the bimetallic elements are cobalt and manganese respectively; and the specific bimetallic structure of the catalyst is MnCo2O 4.5 .

2. The catalyst according to claim 1, characterized in that The specific surface area of ​​the catalyst is 63.33 to 113.35 m 2 / g; the catalyst achieves a nearly 100% ozone removal efficiency under normal temperature and high humidity conditions and maintains stable and efficient operation for at least 100 hours.

3. The method for preparing the catalyst for ozone decomposition according to claim 1, characterized in that: The following steps are involved: (1) Grinding cobalt nitrate and a chelating agent in a mortar, then adding a nitrate precursor of the Mn element, adjusting the rheological phase and continuing grinding; (2) As the liquid water content decreases during the grinding process, a small amount of solvent is added to fully grind to obtain a rheological phase mixed metal solution; (3) The rheological phase mixed metal solution obtained by grinding is transferred to a reaction tank, heated and activated in an oven, and then subjected to solid-liquid separation, washing, drying, and calcination in sequence to obtain the catalyst.

4. The method for preparing a catalyst for ozone decomposition according to claim 3, characterized in that: In step (1), the chelating agent is oxalic acid dihydrate; and the nitrate precursor of the Mn element is a manganese nitrate solution.

5. The method for preparing a catalyst for ozone decomposition according to claim 3, characterized in that: In step (1), the molar ratio of cobalt nitrate to chelating agent oxalic acid dihydrate is (0.8-1.2):

1.

6. The method for preparing a catalyst for ozone decomposition according to claim 3, characterized in that: In step (2), the solvent is deionized water.

7. The method for preparing a catalyst for ozone decomposition according to claim 3, characterized in that: In step (3), the conditions for heating and activating the rheological phase mixed metal solution are: heating at 100-110° C. for 7-9 hours.

8. The method for preparing a catalyst for ozone decomposition according to claim 3, characterized in that: In step (3), the molar ratio of cobalt element to manganese element in the rheological phase mixed metal solution is 1:(4.5-5.5).

9. The method for preparing a catalyst for ozone decomposition according to claim 3, characterized in that: In step (3), the drying conditions are: drying at 100-110° C. for 11-13 h; The calcination conditions are: calcination at 450-550°C for 5-7h.

10. The catalyst according to claim 1 is used for catalytic decomposition of ozone, characterized in that: It is used in various low-concentration ozone pollution sources and ultraviolet photolysis terminal ozone decomposition; ozone pollution sources include air purifiers, sterilization cabinets, and printers.

Citation Information

Patent Citations

  • Catalyst for ozonolysis, preparation method and application thereof

    CN117861681A

  • Manganese-based composite oxide catalyst for catalytically decomposing ozone, and preparation method of manganese-based composite oxide catalyst

    CN102600861A

  • High-efficiency moisture-proof ozonolysis catalyst and preparation method thereof

    CN106824218A

  • Denitration catalyst and preparation method thereof

    CN107175103A

  • Preparation method of manganese-based composite metal oxide ozonolysis catalyst

    CN109833868A

Cited By

  • Preparation of MnCoOx composite catalyst and application of MnCoOx composite catalyst in catalytic oxidation of formaldehyde at room temperature

    CN120502335A